Overlap syndrome of anti-aquaporin-4 positive neuromyelitis optica spectrum disorder and mixed connective tissue disease: a case report - Wang, Ziyu; Wu, Ling; Zhang, Zhihao; Zhang, Chenyang; Jia, Ertao; Geng, Hongling (Frontiers in Immunology, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is an immune-mediated inflammatory demyelinating disease affecting the optic nerve and spinal cord. NMOSD frequently coexists with other autoimmune diseases. However, its concurrence with mixed connective tissue disease (MCTD) is rather rare and often overlooked. This study reports the first case in China of aquaporin-4 immunoglobulin G (AQP4-IgG) seropositive NMOSD preceding MCTD with long-term follow-up. Between 2016 and 2024, the patient successively developed left lower limb numbness, hiccups, vomiting, facial numbness, Raynaud’s phenomenon, finger swelling, digital sclerosis, and synovitis. Acute-phase management involved pulse steroid therapy, while remission maintenance utilized azathioprine, mycophenolate mofetil, rituximab, and inebilizumab for relapse prevention. This paper presents this case and reviews other cases of NMOSD combined with MCTD, aiming to contribute to the clinical understanding and management of this rare condition.